1994
DOI: 10.1007/bf01311173
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of the S protein of transmissible gastroenteritis virus expressed in baculovirus

Abstract: Seven fragments of the spike (S) gene cDNA of transmissible gastroenteritis virus (TGEV), as well as the full length cDNA, were cloned and expressed in baculovirus vectors. Piglets were immunized with cells infected with the recombinant viruses. Each of the recombinants induced TGEV-specific antibodies detected in a fixed cell enzyme immunoassay. The amino terminal half of the S protein, containing all four major antigenic sites (A, B, C and D), and encoded by a 2.2 kb fragment of the S gene, induced virus neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…As the major inducer of TGEV-neutralizing antibodies, the S protein has been used mainly for the induction of protective immunity to TGEV and four major antigenic sites (A, B, C and D) have been defined on the aminoterminal domain [4,5]. Earlier studies have shown that the intact globular N-terminal half of the S protein is sufficient to achieve a protective immune response equivalent to that induced by the full S protein [6].…”
Section: Introductionmentioning
confidence: 99%
“…As the major inducer of TGEV-neutralizing antibodies, the S protein has been used mainly for the induction of protective immunity to TGEV and four major antigenic sites (A, B, C and D) have been defined on the aminoterminal domain [4,5]. Earlier studies have shown that the intact globular N-terminal half of the S protein is sufficient to achieve a protective immune response equivalent to that induced by the full S protein [6].…”
Section: Introductionmentioning
confidence: 99%
“…Baculovirus-infected cells containing the N-terminal fragment of the S-antigen induced neutralizing serum antibodies in piglets (Tuboly et al 1994). Furthermore, oral immunization of piglets using S-antigen-recombinant porcine adenovirus induced both neutralizing antibodies in sera and mucosal antibodies in the intestine (Tuboly et al 2001).…”
Section: Review Of Past Efforts To Produce Tgev Vaccinesmentioning
confidence: 97%
“…Because the baculovirus expression system permits the production of high quantities of foreign proteins in secreted form and the preservation of the native conformation of glycoproteins, including posttranslational modifications such as N-glycosylation, this system represents an attractive method for production of diagnostic reagents. 20,27 The objectives of this study were to simplify blocking ELISA procedures by using recombinant baculovirus S protein antigen for coating and to evaluate its potential for large-scale testing. Comparison of the sera of TGEV-infected, PRCV-infected, and negative control animals revealed that at 21-28 PID blocking § Percentage of pigs that tested positive.…”
Section: Discussionmentioning
confidence: 99%
“…15 The spike (S) glycoprotein is 1 of the 4 structural TGEV/PRCV proteins, but only the S protein contains epitopes that induce virus-neutralizing antibodies. 27 The S glycoprotein contains 4 major antigenic sites (A, B, C, D), antibodies to which can be found in the serum of TGEV-infected pigs. The loss of antigenic epitope D on PRCV strains enables the differential di-agnosis of TGEV and PRCV by the use of monoclonal antibodies (MAbs) to epitope D.…”
mentioning
confidence: 99%